Indonesia and The New Challenges: Multiculturalism, Identity, and Self Narration - Wening Udasmoro, Hasse J (Sekolah Pascasarjana UGM, 2011)
Indonesia and The New Challenges: Multiculturalism, Identity, and Self Narration